DEGRADASI FUNGSI, MAKNA DAN NILAI BUDAYA OKO’ MAMA PADA KOMUNITAS TUTUR UAB METO’ - Diaspora Tualaka (LITERA : Jurnal Bahasa Dan Sastra, 2018)
oko'mama culture in Uab Meto community daily life, (AtoinMeto) in Timor Tengah Selatan district in Timor Island. This Oko 'Mama culture is one of thesymbols that explains the identity of Atoin Meto (Timorese). Based on observations, interviewsand semantic analysis it can be concluded that Oko 'Mama is seen as a structured symbol thatexplains the existence of meto' community life. The results of the study and analysis show thatOko 'Mama functions as a means and symbol of approach, social interaction, tie / liaison, kinship,unifying, reconciliation, controller, case breaker, receptionist, respect and appreciation, agreementcontrol status and as a material storage material betel, areca nut, lime and tobacco. Through thisoko 'mama culture, we can look at the social life of the Uab Meto community known as AtoinMeto. Based on the findings in the field, in fact, it can be concluded that this tradition has a strongexistence in encouraging Atoin Meto to carry out daily social activities, but in the currentdevelopment of Oko 'Mama culture has undergone a shift in its function. This can be seen fromthe purpose of using Oko 'Mama, which was originally an adhesive for culture to turn into apolitical goal.Keywords: maintenance, form, function and symbolic meaning, oko 'mamaABSTRAKTulisan ini menjelaskan gambaran nyata tentang budaya oko’mama dalam kehidupan komunitastutur Uab Meto (Atoin Meto) di kabupaten Timor Tengah Selatan di pulau Timor. Budaya okomama ini adalah salah satu simbol yang menjelaskan tentang identitas Atoin Meto (orang Timor).Berdasarkan pengamatan,wawancara dan analisis semantik dapat disimpulkan bahwa oko’ mamadipandang sebagai simbol berstruktur yang menjelaskan tentang keberadaan kehidupanmasyarakat meto’. Hasil kajian dan analisi menunjukan bahwa oko’ mama berfungsi sebagaisarana dan dan simbol pendekatan, interaksi sosial, pengikat/penghubung,kekerabatan,pemersatu, pendamai, pengontrol, pemutus perkara, penerima tamu,penghormatan danpenghargaan, status pengontrol kesepakatan dan sebagai wadah penyimpaan materi sirih,pinang, kapur, dan tembakau. Melalui budaya oko’ mama ini kita dapat meneropong kehidupanbersosial komunitas tutur uab meto yang dikenal dengan sebutan atoin meto. Berdasarkan temuandi lapangan secara faktual dapat disimpulkan bahwa budaya oko’ mama memiliki eksistensi yangkuat dalam memberikan semangat bagi atoin meto untuk melaksanakan kegiatan sosial sehariharinamun dalam perkembangan jaman saat ini budaya oko’ mama telah mengalami pergeseranfungsinya. Hal ini terlihat dari tujuan pemakaian oko’ mama yang semula sebagai perekat budayaberalih menjadi tujuan politis.Kata kunci: kebertahanan, bentuk, fungsi dan makna simbolis, oko’ mama